ITERA Astronomical Observatory Information System - Muhammad Habib Algifari; Winda Yulita; Eko Dwi Nugroho (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
In the current information age, data is a valuable asset for companies [1]. Technological advances encourage the digitization of information in almost all fields of science, including astronomy. Technological developments make it easy to access open data in the public domain. The availability of open data will encourage the acceleration of research. ITERA Astronomical Observatory is an observatory located in Lampung. This observatory is claimed to be the largest in Southeast Asia [3]. To face the challenges in the digitization of information, ITERA Astronomical Observatory plans to build an information system specifically for Storing and handling astronomical data